Should the patella be everted during primary total knee arthroplasty? A systematic review of overlapping meta-analyses. (18th February 2019) - Grassi, Alberto; Compagnoni, Riccardo; Ferrua, Paolo; Pasqualotto, Stefano; Zaolino, Carlo; Zaffagnini, Stefano; Randelli, Pietro
Patellar eversion during total knee arthroplasty (TKA) is a debated issue. The aim of this study is to perform a review of overlapping meta-analyses analyzing clinical outcomes of patellar eversion compared to noneversion. A search was performed in PubMed\MEDLINE, Scopus, and Cochrane Library. Inclusion criteria were meta-analysis of randomized controlled trials (RCTs) or quasi-RCTs;l comparison between TKAs with or without patellar eversion; and at least one outcome, such as reoperation rate, pain, and functional scores. Meta-analyses were evaluated with the A Measurement Tool to Assess Systematic Review (AMSTAR) score, addressing the most relevant one with the Jadad algorithm. Three meta-analyses were identified and included in this review. No significant differences were found regarding complications, quadriceps strength, functional, and radiological outcomes. The meta-analysis by Zan et al. was selected as the best available one. Patellar eversion group showed a shorter tourniquet time but a longer skin incision. In conclusion, eversion and noneversion techniques did not demonstrate any significant or clinically relevant difference. Level of Evidence: Level II, systematic review of meta-analyses